Molecular Dynamics Simulations of Cross‐Linked Phenolic Resins Using a United‐Atom Model. Issue 4 (22nd March 2018) - Izumi, Atsushi; Shudo, Yasuyuki; Hagita, Katsumi; Shibayama, Mitsuhiro
Abstract: A new molecular modeling algorithm for conducting large‐scale molecular dynamics simulation studies of cross‐linked phenolic resins is developed using a united‐atom model. A phenol–formaldehyde polycondensation system is simulated by a pseudoreaction algorithm taking into consideration (i) the difference in the experimental reaction rate constants at ortho and para positions of phenolic units and (ii) the geometry of the reactants. To avoid formation of locally strained cross‐linked structures that can be generated in a typical cutoff‐distance‐based reaction scheme, a geometrical judgment constraint is applied in the reaction procedure. With this algorithm, cross‐linked network structures of phenolic resins with a maximum conversion (α) of 0.90 are obtained from 10 000 phenols. The density and the tensile modulus of the structure with α of 0.90 at 300 K are 1.2 g cm −3 and 5.4 GPa, respectively. This is in good agreement with experimental values. The strain‐free, highly cross‐linked network structures of phenolic resins exhibit a higher density and tensile modulus compared with structures generated in the absence of the geometrical cutoff. This result demonstrates that the geometrical judgment constraint can effectively avoid the formation of distorted and strained local structures and is necessary for accurate modeling of highly cross‐linked phenolic resins. Abstract : A new molecular modeling algorithm for conducting large‐scale molecular dynamics simulation studies of cross‐linked phenolic resins is developed using a united‐atom model.